The verbal system in late enlightenment Hebrew - Kahn, Lily. (Studies in Semitic Languages and Linguistics, 2009)
This book constitutes the first detailed corpus-based analysis of the verbal morphology and syntax employed in the Eastern European Maskilic (Jewish Enlightenment) Hebrew prose fiction written between 1857 and 1881. This verbal system exhibits biblical, rabbinic and medieval elements as well as unprecedented features and similarities to Israeli Hebrew and Yiddish. The first section of the work offers a selective examination of maskilic verbal morphology, while the second section constitutes a thorough examination of the functions of the verbal conjugations and the third section surveys selected features of verbal syntax. The work fills a serious gap in the Hebrew philological literature and will therefore be of great relevance to students and scholars of diachronic Hebrew language and linguistics.